House of cards and philosophy : Underwood's republic - Hackett, J. Edward, 1979- (Blackwell philosophy and popculture series., 2016)
"Is Democracy overrated? Does power corrupt? Or do corrupt people seek power? Do corporate puppet masters pull politicians strings? Why does Frank talk to the camera? Can politics deliver on the promise of justice? House of Cards depicts our worst fears about politics today. Love him or loathe him, Frank Underwood has charted an inimitable course through Washington politics. He and his cohorts depict the darkest dealings within the gleaming halls of our most revered political institutions. These 24 original essays examine key philosophical issues behind the critically-acclaimed series questions of truth, justice, equality, opportunity, and privilege. The amoral machinations of Underwood, the ultimate anti-hero, serve as an ideal backdrop for a discussion of the political theories of philosophers as diverse as Plato, Aristotle, Nietzsche, Machiavelli, Hobbes, and Marx. From political and corporate ethics, race relations, and ruthless paragmatism to mass media collusion and sexual politics, these essays tackle a range of issues important not only to the series but to our understanding of society today"--Provided by publisher.